Language development and acquisition in early childhood - Salwa Saeed Al-Harbi (Intelektual Pustaka Media Utama, 2020)
The paper discussed in detail the process of language development and the process of language acquisition in early childhood. It also gave a brief overview of the theoretical frame of reference of language development. The paper included an in depth explanation of the importance and impact of over-exposure for early second language acquisition and it answered the question of whether language learning could turn into a language acquisition after what Noam Chomsky referred to as the “critical period”. The paper concluded that even after the Chomskian critical period learners who got overexposed to the target language can acquire the language and it can be equivalent to their first language. The paper discussed two major kinds of motivations at play in the process of second language acquisition: (1) Curiosity: A desire to better understand a group of people and their way of life , and (2) Empathy: Upon repeated exposure, one might come to the conclusion that this group of people has a more sensible handle on things, and thus identifies with them.